The Effect of Fixed Asset Intensity, Profitability, and Audit Quality on Tax Avoidance: IDX Mining Companies 2021-2024 - Ailsa Fitrah Maharani Candra; Ahmad Rahbani Sulaiman Sirait (Universitas Pancasakti Tegal, 2026)
This study aims to analyze the effect of fixed asset intensity, profitability, and audit quality on tax avoidance in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. This study employed a quantitative approach using secondary data obtained from companies’ annual financial statements. The sample was selected through purposive sampling, resulting in 126 observations. Data were analyzed using multiple linear regression with firm size as a control variable. The research results show that fixed asset intensity has no effect on tax avoidance. Profitability has a positive effect on tax avoidance, while audit quality has a negative effect on tax avoidance. These findings indicate that companies with high profitability tend to engage in more tax avoidance, whereas better audit quality can curb tax avoidance practices. This study provides empirical evidence on the factors that influence tax avoidance in mining companies in Indonesia.